The Psychological Well-being of Adolescents in Suburban Communities in Indonesia: Online Survey - Barida, Muya; Widyastuti, Dian Ari; Krisphianti, Yuanita Dwi; Martaningsih, Sri Tutur; Ahmad, Aslina (Angstrom Centre of Education, 2024)
The psychological well-being condition of adolescents need to be considered. In this article, we explore the condition of psychological well-being whose aspects consist of autonomy, environmental mastery, personal growth, positive relations, purpose in life, and self-acceptance of adolescents through a psychological well-being scale submitted online. A total of 2,884 junior high school-aged adolescents from the Special Region of Yogyakarta filling the psychological well-being scale. We found that 6% of adolescents' psychological well-being was in the very low category, 22% was in the low category, 43% was in the medium category, 20% was in the high category, and 8% was in the very high category. This category can be a consideration for teachers that the psychological well-being of adolescents or students can be improved so that their academic performance can increase. Psychological well-being is something that must be strengthened because it is one of the Sustainable Development Goals (SDG) in Indonesia.